Tradition of Burning Barges in Rokan Hilir Regency: Arts and Culture Studies - Esi Gusrini, Esi; Agustina, Agustina (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
Every society inherits traditions from its predecessors, creating a cultural continuum that defines social identity. In Indonesia, one of the unique cultural traditions is the Barge Burning Ritual, known as "Go Ge Cap Lak," which is deeply rooted in the Chinese ethnic community of Bagansiapiapi, Riau. This annual ritual, celebrated on the 16th day of the fifth month of the lunar calendar, serves as a tribute to ancestors who migrated to Bagansiapiapi in search of a better life. The ritual involves burning a replica of a barge to symbolize their commitment to settling in the new land, as well as to honor the sea gods Ki Hu Ong Ya and Tai Sun.This study employs a qualitative descriptive approach using Feldman’s theory of art criticism, encompassing description, formal analysis, interpretation, and evaluation. Data collection methods include observation, in-depth interviews with traditional leaders and the Mak Teduh community, and documentation review. The study applies source triangulation for data reliability and follows a systematic process of data collection, reduction, presentation, and conclusion. The findings reveal that the Barge Burning Ritual holds significant historical, religious, and cultural meanings. It reflects the Chinese community’s struggle, resilience, and devotion to their deities. The ritual is also believed to influence economic prosperity, as the direction in which the barge falls after burning is interpreted as a sign of fortune—whether from the land or the sea. Additionally, the ritual fosters communal solidarity and preserves ancestral heritage. However, differing religious perspectives within the broader community influence participation and perception of the event. In conclusion, the Barge Burning Ritual is a profound manifestation of cultural identity, spiritual belief, and historical commemoration. It serves as both a means of worship and a cultural spectacle that strengthens ethnic cohesion while contributing to the region’s cultural tourism. Future research could explore its socio-economic impact and its role in intercultural dialogue.